45 Experience of 5 years of balloon pulmonary angioplasty in a single centre: safety and short-term results. (8th December 2021) - Guarino, Daniele; Palazzini, Massimiliano; Saia, Francesco; Dardi, Fabio; Taglieri, Nevio; De Lorenzis, Alessandro; Ballerini, Alberto; Rotunno, Mariangela; Magnani, Ilenia; Donato, Federico; Bertozzi, Riccardo; Marrozzini, Cinzia; et al.
Abstract: Aims: Balloon pulmonary angioplasty (BPA) has recently been developed as a treatment strategy for chronic thromboembolic pulmonary hypertension (CTEPH) but efficacy and technical safety have to be established. We examine the effects of BPA on patients with inoperable disease or residual pulmonary hypertension (PH) after pulmonary endarterectomy (PEA). Methods and results: From 2015 to 2020 we enrolled symptomatic inoperable CTEPH patients and patients with residual PH after PEA. At baseline and 3 months after last BPA session patients underwent clinical evaluation, 6-min walking distance (6MWD), and right heart catheterization. Friedman test with Bonferroni post-hoc pairwise analysis was used. Fifty patients [male 42%, median age 68 (51–74) years, 42 inoperable, and 8 with residual PH after PEA] were treated for a total of 156 sessions (median 2 sessions/patient); during each session we treated 2.3 (2.2–2.7) vessels. Results are shown in the Table. Forty-nine patients were treated with medical therapy before BPA (19 with combination therapy). Five pulmonary artery dissection and two haemoptysis with clinical impairment were documented during the procedures; 37 patients had lung injury (radiographic opacity with/without haemoptysis and/or hypoxaemia), none had renal dysfunction, 7 patients had access site complications. Seven patients died during follow-up (none within 30 days from the procedure) because of sepsis (1), heart failure (1), cancer (2), arrhythmic storm (2), and sudden death in patients with severe coronary atherosclerosis (1). Conclusions: BPA is a safe and effective treatment able to improve symptoms and haemodynamic profile.